Eliminating a Barrier to Access: Waiving or Reducing Fees for Public Records in Florida - Virginia Hamrick (Brechner Center for Freedom of Information, University of Florida, 2021)
Florida, the Sunshine State, is one of the few states that includes a right of access to public records in its constitution. While Florida guarantees a right of access to every person, special service charges and high costs for public records restrict access to only requestors with the financial resources to pay for requests. Some agencies assert that waiving fees for requests that have a public interest would be significantly costly. This article builds on research showing that a fee waiver for requests made in the public interest would have minimal effect on Florida municipalities. This article analyzes agency public records logs to assess how a fee waiver for requests made for noncommercial purposes and in the public interest would affect state agencies. This article finds that only 14% of requests reviewed would be entitled to a fee waiver.